Development of a Learning Model for Passing in Volleyball Based on a Small Game for Students of Az-Zahrah Islamic Primary School, Palembang City - Trisnawati, Ayu; Handayani, Widya; Lestari, Hikmah (PPSDP International Journal of Education, 2024)
The aim of this study was to determine whether the development of valid volleyball upper passing learning for Palembang city elementary school students. This is a research and. The development approach that we use is ADDIE. The subjects of this study were Az-Zahrah Islamic Elementary School students represented by class V for field trials or implementation of volleyball top passing learning development products. The trial subjects totaled 25 students. Based on the data that we found through observation activities, that the environment still really needs a lot of games that can be used for physical education learning. While in reality, teachers are still very minimal references to games that can be used for the learning process, especially games that contain elements of special skill motion specifications such as those found in the upper passing technique of volleyball games.